Characteristics of a Cold-Adapted L-glutaminase with Potential Applications in the Food Industry - Ferreira, Flavia Vanina; Herrmann Andrade, Andreina M.; Binolfi, Andrés; Calabrese, Carla D.; Mac Cormack, Walter Patricio; Musumeci, Matias Alejandro (Applied Biochemistry and Biotechnology)
L-glutaminases are enzymes that catalyze the hydrolysis of L-glutamine, producing L-glutamate and ammonium, and they have promising applications in pharmaceutical and food industries. Several investigations have focused on thermo-tolerant L-glutaminases; however, studies on cold-adapted L-glutaminases have not been reported. These enzymes could be useful in the food industry because they display high catalytic activity at low and room temperatures, a valuable feature in processes aimed to save energy. Besides, they can be easily inactivated by warming and are suitable to prevent decomposition of thermo-labile compounds. The objectives of this work were to characterize the L-glutaminase from the Antarctic bacterium Bizionia argentinensis and analyze its capability as flavor enhancer of protein hydrolysates. The enzyme was heterologously expressed and purified from Escherichia coli, obtaining optimum and homogeneous yields. Kinetic parameters Km and Vmax were located at the lower and upper range of values reported for L-glutaminases, suggesting high catalytic efficiency. Optimum temperature was 25 °C, and the enzyme conserved around 90% of maximum activity at 0 °C and in presence of 15% (v/v) ethanol and methanol. In saline conditions, the enzyme conserved around 80% of maximum activity in 3 M NaCl. Analysis of structural model suggested cold-adaptation features such as low Arg/(Arg+Lys) ratio and fewer intramolecular interactions than mesophilic and thermo-tolerant L-glutaminases. This work provides a novel cold-adapted L-glutaminase with promising features in the food industry. Fil: Ferreira, Flavia Vanina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro de Investigaciones y Transferencia de Entre Ríos. Universidad Nacional de Entre Ríos. Centro de Investigaciones y Transferencia de Entre Ríos; Argentina Fil: Herrmann Andrade, Andreina M. Universidad Nacional de Entre Rios. Facultad de Cs. de la Alimentación. Departamento de Cs. de Los Alimentos; Argentina Fil: Binolfi, Andrés. Consejo ...